Internalization of Legal, Political, and Economic Values within the Framework of Islamic Civilization in Primary Education - Afifi, Ruhana (Proceedings: International Seminar On Educational Studies, 2025)
This study analyzes the process of internalizing legal, political, and economic values within the framework of Islamic civilization (tamadun Islam) in primary education in Indonesia, Brunei Darussalam, and Malaysia. Using a literature review method, this study examines scientific literature and educational policies to assess the role of Islamic values in fostering moral awareness and character building among students. The findings show that the internalization of legal values (justice and responsibility), political values (trust, deliberation, and leadership), and economic values (honesty and prosperity) form the basis for shaping insan kamil, or individuals with moral and intellectual balance. This internalization process takes place through formal learning, school culture, and teacher role modeling. Cross-country comparisons show that Brunei and Malaysia implement systematic Sharia-based education policies, while Indonesia implements them contextually through the Merdeka Curriculum. This study emphasizes the importance of strengthening education based on Islamic civilization to encourage a balance between worldly achievements and spiritual development from the primary education level onwards.